Computational Secrecy by Typing for the Pi Calculus - Abadi, Martin; Corin, Ricardo; Fournet, Cédric (Fourth ASIAN Symposium on Programming Languages and Systems (APLAS 2006), 2006)
We define and study a distributed cryptographic implementation for an asynchronous pi calculus. At the source level, we adapt simple type systems designed for establishing formal secrecy properties. We show that those secrecy properties have counterparts in the implementation, not formally but at the level of bitstrings, and with respect to probabilistic polynomial-time active adversaries. We rely on compilation to a typed intermediate language with a fixed scheduling strategy. While we exploit interesting, previous theorems for that intermediate language, our result appears to be the first computational soundness theorem for a standard process calculus with mobile channels.